Sanctions: war and economic consequences - Frankel, Jeffrey (Henry Stewart Talks, 2022)
Russia, Ukraine, US, EU, Sanctions, Food shortage, Economic growth, China, Rare earth, Alternative energy sources, Nuclear energy, National spending, Market economy, Command economy